Clinical significance of enzyme induction and inhibition - Brøsen, Kim (Henry Stewart Talks, 2007)
Metabolic drug interactions, Prediction of significant drug interactions, Cytochrome P450 (CYP) enzymes, Identifying clinically important mechanisms, Therapeutic index, Clinical dose titration
Updated at 2016/07/27